Closure of tailings facilities: Current practice review and guidelines for success - Mark, Robins (My University, 2006)
This research project has been prepared to satisfy the requirements of the University of the Witwatersrand, Faculty of Engineering and the Built Environment for the degree of Master of Science (Civil) in Geotechnical Engineering and Materials (50/50). Contained within the project is a review of international past and current tailings facility closure techniques. Guidelines and minimum requirements for successful closure have been developed and are presented.
Faculty of Engineering and the Built Environment School of Civil Engineering 9311276v
Keywords: Engineering; Guidelines